Genetic Variants Predict Optimal Timing of Radiotherapy to Reduce Side-effects in Breast Cancer Patients. Issue 1 (January 2019) - ,; Azria, David; Brookes, Anthony; Burr, Tom; Chang-Claude, Jenny; Davidson, Susan; De Ruysscher, Dirk; Dunning, Alison; Elliott, Rebecca; Gutiérrez Enríquez, Sara; Lambin, Philippe; Rancati, Tiziana; et al.
Abstract: Aims: Radiotherapy is an important treatment for many types of cancer, but a minority of patients suffer long-term side-effects of treatment. Multiple lines of evidence suggest a role for circadian rhythm in the development of radiotherapy late side-effects. Materials and methods: We carried out a study to examine the effect of radiotherapy timing in two breast cancer patient cohorts. The retrospective LeND cohort comprised 535 patients scored for late effects using the Late Effects of Normal Tissue-Subjective Objective Management Analytical (LENT-SOMA) scale. Acute effects were assessed prospectively in 343 patients from the REQUITE study using the CTCAE v4 scales. Genotyping was carried out for candidate circadian rhythm variants. Results: In the LeND cohort, patients who had radiotherapy in the morning had a significantly increased incidence of late toxicity in univariate ( P  = 0.03) and multivariate analysis ( P  = 0.01). Acute effects in the REQUITE group were also significantly increased in univariate analysis after morning treatment ( P  = 0.03) but not on multivariate analysis. Increased late effects in the LeND group receiving morning radiotherapy were associated with carriage of the PER3 variable number tandem repeat 4/4 genotype ( P  = 6 × 10 −3 ) and the NOCT rs131116075 AA genotype ( P  = 5 × 10 −3 ). Conclusion: Our results suggest that it may be possible to reduce toxicity associated with breast cancer radiotherapy by identifying gene variants that affect circadian rhythm and scheduling for appropriate morning or afternoon radiotherapy. Highlights: Radiotherapy for breast cancer in the morning causes worse acute and late toxicity. Alleles of two circadian rhythm genes predict worse outcome in the morning. The results will allow genetically determined chronoradiotherapy.